Monetary Policy and Wealth Effects: The Role of Risk and Heterogeneity - Nicolas Caramp; Dejanir H. Silva (Center for Economic Studies and ifo Institute (CESifo), 2024)
We study the role of asset revaluation in the monetary transmission mechanism. We build an analytical heterogeneous-agents model with two main ingredients: i) rare disasters; ii) heterogeneous beliefs. The model captures time-varying risk premia and precautionary savings in a setting that nests the textbook New Keynesian model. The model generates large movements in asset prices after a monetary shock but these movements can be neutral on real variables. Real effects depend on the redistribution among agents with heterogeneous precautionary motives. In a calibrated exercise, we find that this channel accounts for the majority of the transmission to output.
Keywords: E21; E44; E52; G12; 330; monetary policy; wealth effects; asset prices; aggregate risk; heterogeneity beliefs